Implementasi Kebijakan Penanggulangan Kemiskinan Dalam Program Rumah Layak Huni di Kota Gorontalo - Pateda, Novriyanti; Sulila, Ismet; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research aims to investigate (1) The stages of the Policy Implementation Process of the Livable House Program in Gorontalo City, with sub-focuses on Planning, Implementation, and Evaluation. (2) The factors supporting implementing the Livable House Program Policy in Gorontalo City, with sub-focuses on Communication, Resources, Disposition, and Bureaucratic Structure. This research method utilizes a qualitative approach with a descriptive qualitative research design, employing data collection techniques such as observation, interviews, and documentation. Based on the result of the research found in the field, it is evident that (1) The stages of the Policy Implementation Process of the Livable Housing Program in Gorontalo City, focusing on Planning, Implementation, and Evaluation, have been effectively implemented in accordance with the Gorontalo City’s Regional Regulation Number 5 of 2018. Nevertheless, several challenges remain, including; budget limitations, budget disbursement stages, and the proposal submissions process. Therefor, the government must ensure efficient, transparent, and accountable budget management to overcome these challenges. (2) The Factors supporting the Implementation of the Livable House Program Policy in Gorontalo City, such as Communication, Resources, Disposition, and Bureaucratic Structure, have been successfully implemented.